Labour market reform for more and better quality jobs in Italy - Jin, Yosuke (OECD Publishing, 2015)
A well-functioning labour market is indispensable to promote job creation, increase living standards, and develop a cohesive society. In Italy, the various deficiencies of the labour market have resulted in high unemployment, low labour force participation and job-skill mismatch. These deficiencies have contributed to the problem of allocation of resources, income distribution, and low productivity, reducing people's well-being. The current government, following on past governments' reforms, is introducing a package of labour market reforms - the Jobs Act - to improve the labour market in a consistent way. The reform will make the labour market more flexible and inclusive, and reduce duality. The long-lasting problem of effective enforcement will need to be overcome, with an increased focus on rapid implementation by the current government. A set of well-designed institutions, not only labour market policies but also the education system and product market regulation, would encourage higher labour force participation, especially among women, and produce more and better quality jobs in a more skill-intensive economy. This Working Paper relates to the 2015 OECD Economic Survey of Italy (www.oecd.org/eco/surveys/economic-survey-italy.htm)
Keywords: Economics; Italy